Knowledge Management System Pengajuan Nasabah Pembiayaan pada BJB Syariah - Opitasari Opitasari (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2022)
BJB Syariah has several work units, including branch heads, operational managers, back offices, tellers, customer service and marketing. In recording the submission of financing customers, BJB Syariah still performs the documentation using paper media so that the knowledge obtained is still difficult to process. It makes the customer data lost or not neatly arranged, leading to a relatively long period of searching the data. Therefore, it is necessary to have a system that can provide convenience in recording customer submissions in the form of a Knowledge Management System. The system is expected to produce information that is related to customers and can be documented as evidence of data storage in real time. The system development method used is Rapid Application Development (RAD) starting from the Requirement Planning stage to the Workshop Design stage. The design tool used is the Unified Modeling Language (UML). The system is made using software Preprocessor Home Page (PHP) as a programming language and MySQL as database management. The designing of this web-based knowledge management system produces reports containing customer data and reports on financing submission on a regular basis.